2018
DOI: 10.3855/jidc.10000
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori 23S rRNA gene mutations associated with clarithromycin resistance in chronic gastritis in Vietnam

Abstract: Introduction: Data about the prevalence of the A2142C, A2142G, and A2143G mutations in 23S rRNA gene is still limited. The aim of this study was to determine the prevalence of these mutations in 23S rRNA gene of H. pylori vietnamese strains. Methodology: One hundred and sixty-nine patients with H. pylori-positive chronic gastritis were examined. H. pylori was detected by rapid urease test and Polymerase chain reaction (PCR). Total DNA was extracted from gastric biopsy specimens. A2142C, A2142G, and A2143G muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…However, the number of sequenced samples (25) was relatively small. The screening of 169 patients positive for chronic gastritis in Vietnam, using PCR-RFLP, found the A2143G mutation in 36.1% of samples and the A2142G mutation in 3.6%; however, it failed to detect the A2142C mutation [ 29 ].…”
Section: Molecular Mechanisms Of Antibiotic Resistancementioning
confidence: 99%
“…However, the number of sequenced samples (25) was relatively small. The screening of 169 patients positive for chronic gastritis in Vietnam, using PCR-RFLP, found the A2143G mutation in 36.1% of samples and the A2142G mutation in 3.6%; however, it failed to detect the A2142C mutation [ 29 ].…”
Section: Molecular Mechanisms Of Antibiotic Resistancementioning
confidence: 99%
“…Comments: The results of clinical trials conducted during the last 5 years in Vietnam showed that the primary resistance rates of clarithromycin and metronidazole were very high, up to 34.1 and 69.4%, respectively ( 4 , 38 ). Recent data also show that the resistance rates of amoxicillin and levofloxacin tend to increase significantly ( 39 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…The coexistence of multiple H. pylori strains in the same patient may be the result of simultaneous colonization, which has been described in many studies, 45,46 including in the Vietnamese population. 47…”
Section: Discussionmentioning
confidence: 99%
“…The vacA genotyping results also demonstrated that 27.9% of patients had multiple vacA genotypes in the same gastric biopsy ( s1/m1m2 , s1s2/m2 , and s2/m1m2 ), suggesting multiple strains infections. The coexistence of multiple H. pylori strains in the same patient may be the result of simultaneous colonization, which has been described in many studies, 45,46 including in the Vietnamese population 47 . In addition, PCR‐based methods are highly sensitive but fail to differentiate between alive and dead bacteria, which can lead to false positive results.…”
Section: Discussionmentioning
confidence: 99%